Material Trajectories: Designing With Care? - Koffi Agbodjinou, Sename; Ahrensfeld, Viola S; Boehnert, Joanna; Bulling, Jessica; Büsse, Michaela; De Visscher, Emile; Kirschner, Roman; Kretzer, Manuel; Kundoo, Anupama; Müller, Martin; Peluso, Fara; Schäffner, Wolfgang; et al. (Material Trajectories Designing With Care?, 2023)
Material Trajectories: Designing With Care? turns towards material-driven design processes with the aim of relocating technoscientific trajectories. Concerned with new forms of caretaking, it combines positions from the extended fields of design research and humanities scholarship including practice-based approaches. The contributions explore current ecological conditions through multiple acts of making-with and seek to complicate questions of sustainability, livability, and cooperation. In reassessing the status quo in design and architecture as material practices, they provide outlines for a nuanced reading of these worldmaking processes and ask what different ways of designing with care and complicity might entail.